2016
DOI: 10.7324/japs.2016.60928
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Crataeva nurvala extracts as antioxidant, antiproteolytic and cytotoxic against hepato-carcinoma and mouse melanoma cell lines

Abstract: The crude extracts from stem bark of Crataeva nurvala Buch.-Ham containing naturally occurring antioxidants were screened for their most abundant phytosecondary metabolite, antiproteolytic and cytotoxic properties. The antioxidant activity of the extracts was determined by DPPH radical scavenging activity, Ferric reducing power and β Carotene linoleic acid assay. The antiproteolytic activity of crude extracts was determined by inhibition of trypsin-induced hydrolysis of BSA. The IC50 of cytotoxic effect on Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…The qualitative phytochemical screening of methanol extract of stem bark of C. nurvala showed the presence of steroids, triterpenoids and alkaloids. Phytochemical screening of methanol extract of stem bark of C. nurvala revealed the presence of steroid and terpenoids as well as alkaloids, phenolics, flavanoids, tannins and saponins (Hade et al, 2016) which supported our results. Sodipo et al (2000) have reported that alkaloids have been associated with medicinal uses for centuries and one of their common biological properties is their cytotoxicity.…”
Section: Qualitative Phytochemical Analysissupporting
confidence: 90%
“…The qualitative phytochemical screening of methanol extract of stem bark of C. nurvala showed the presence of steroids, triterpenoids and alkaloids. Phytochemical screening of methanol extract of stem bark of C. nurvala revealed the presence of steroid and terpenoids as well as alkaloids, phenolics, flavanoids, tannins and saponins (Hade et al, 2016) which supported our results. Sodipo et al (2000) have reported that alkaloids have been associated with medicinal uses for centuries and one of their common biological properties is their cytotoxicity.…”
Section: Qualitative Phytochemical Analysissupporting
confidence: 90%
“…The absorbance was measured at 750 nm. Salicylic acid (5 mg/mL) was used as standard [12,16,21,29]. Xanthine oxidase inhibition assay.…”
Section: Determination Of Total Polyphenols Contentmentioning
confidence: 99%
“…Previously anticancer, antimicrobial, antihypertension, analgesic, antiparasitic, antidiabetic and antioxidant activities of C. adansonii have been reported (Zingue et al, 2016;Adjagba et al, 2017). Cytotoxic studies have been carried out in various genera of the family Capparaceae including C. nurvala (Sinha et al, 2013;Ali et al, 2014;Hade et al, 2016;Parvin et al, 2011) and C. nurvala (Da Silva Ferreira et al, 2013).…”
mentioning
confidence: 99%